2011
DOI: 10.1016/j.biopsych.2010.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Altered MicroRNA Expression Profiles in Postmortem Brain Samples from Individuals with Schizophrenia and Bipolar Disorder

Abstract: Background MicroRNAs (miRNAs) are potent regulators of gene expression with proposed roles in brain development and function. We hypothesized that miRNA expression profiles are altered in individuals with severe psychiatric disorders. Methods Using real-time quantitative PCR, we compared the expression of 435 miRNAs and 18 snoRNAs in post-mortem brain tissue samples from individuals with schizophrenia, individuals with bipolar disorder, and psychiatrically healthy control subjects (n = 35 each group). Detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(190 citation statements)
references
References 31 publications
7
183
0
Order By: Relevance
“…If major depression is due to lack of reward, the analysis of molecular profiles in the nucleus accumbens from CUMS‐induced depression and resilience should help to figure out the role of the nucleus accumbens in major depression and resilience based on molecules analyzed. The alternations of certain genes have not been observed in previous analyses (Bai et al, 2014; Elizalde et al, 2010; Li et al, 2013; Liu et al, 2015; Moreau, Bruse, David‐Rus, Buyske, & Brzustowicz, 2011; Rajkowska et al, 2015; Smalheiser et al, 2012, 2011, 2014), including Cckar , Tshr , Kcnj5 , Alox12 , Slc17a6 , Per2 , Rtn4r , and Nrn1 . These genes in the nucleus accumbens may be newly working for major depression or resilience.…”
Section: Discussionmentioning
confidence: 80%
“…If major depression is due to lack of reward, the analysis of molecular profiles in the nucleus accumbens from CUMS‐induced depression and resilience should help to figure out the role of the nucleus accumbens in major depression and resilience based on molecules analyzed. The alternations of certain genes have not been observed in previous analyses (Bai et al, 2014; Elizalde et al, 2010; Li et al, 2013; Liu et al, 2015; Moreau, Bruse, David‐Rus, Buyske, & Brzustowicz, 2011; Rajkowska et al, 2015; Smalheiser et al, 2012, 2011, 2014), including Cckar , Tshr , Kcnj5 , Alox12 , Slc17a6 , Per2 , Rtn4r , and Nrn1 . These genes in the nucleus accumbens may be newly working for major depression or resilience.…”
Section: Discussionmentioning
confidence: 80%
“…Emerging evidence suggests a strong association between miRNAdependent dysregulation of gene expression and susceptibility to psychiatric disorders, such as SCZ (3,31,32). In particular, previous work has shown that impaired miRNA formation (caused by Dgcr8 deficiency) is one of the genetic factors contributing to the behavioral and neuronal phenotypes associated with 22q11.2 deletions, a well-established SCZ predisposing mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that 70% of known miRNAs are expressed in the CNS, some of which are brain specific or brain-region specific (7), implying that these miRNAs may play a vital role in the development of diseases in the CNS (8). Altered miRNA levels have been found in CSF and postmortem brain of schizophrenia patients (9,10), but no ideal miRNAs have been identified in the circulation that might be used as biomarkers for clinical applications. As plasma and serum samples can be easily collected, it is important to detect circulating miRNAs of interest as diagnostic biomarkers, as opposed to potential biomarkers in other tissues.…”
mentioning
confidence: 99%